Anion‐Binding Macrocycles Operate Beyond the Electrostatic Regime: Interaction Distances Matter. Issue 54 (19th September 2018) - Sengupta, Arkajyoti; Liu, Yun; Flood, Amar H.; Raghavachari, Krishnan
Abstract: Anion recognition impacts many areas of chemistry and often relies on receptors with multiple hydrogen‐bond donors. Previous studies of these donors in small molecules have long promoted the idea that electrostatic interactions alone correlate with association strength, yet this correlation has not been critically evaluated in the framework of larger, macrocyclic receptors. Here, we provide that assessment by evaluating how much electrostatics contributes to the gas‐phase binding energy of macrocyclic receptors with various anions. Whereas small‐molecule complexes behave as expected, we find that electrostatic interactions fail to accurately describe total binding energies of many common macrocyclic receptors: calix[4]pyrroles, dipyrrolyldiketones, indolocarbazoles, amido‐pyrroles, triazolophanes, and cyanostars. This deviation arises from the fact that most macrocycles have multiple points of contact with the anion. Whereas the hydrogen‐bond donors collectively stabilize the anion, the interaction distances are typically larger than equilibrium values seen with small molecules. This leads to increases in the relative contributions of the attractive components such as induction (e.g., induced dipoles) and dispersion, which are found to be as high as 32 % for CH‐donor based tricarbazole triazolophane complex with large polarizable ClO4 − . This study augments previous observations of the importance of dispersion and induction towards anion binding of macrocyclic receptors in solution. Abstract : Size matters : Although electrostatic interactions determine the stabilization of small‐molecule anion binding, in larger macrocyclic complexes the stabilization is also determined by induction and dispersion. This study enables accurate computer‐aided design of anion receptors by accounting for the altered character of the hydrogen bonding in synthetic complexes (see figure).